Consecuencias psicológicas debido a la enfermedad del VIH en una joven de 24 años de la ciudad de Babahoyo - Rendón Herdoiza , Madelín (2023)
The present investigation arises thanks to the care provided to a patient, who had a disturbed psychological condition because she announced that she had tested positive for HIV. There are very few investigations of this nature, of which it is a field that should be more analyzed. The type of research that the case study will have will be the inductive method, accompanied by the narrative research design, then supported by the mixed approach. HIV is a disease that often alters the central nervous system due to the type of medication the patient is consuming, but with it the subject manages to lead a better quality of life. The patient presented a picture of anxiety and moderate depression, of which the presumptive psychodiagnosis was obtained: Anxiety disorder due to illness 300.7 (F45.21) and Depressive disorder due to another medical condition: 293.83, being a comorbid psychopathology.